Spirorchiidiosis (Digenea: Spirorchiidae) and lesions associated with parasites in Caribbean green turtles (Chelonia mydas) - Santoro, M. (2015)
Forty-seven nesting green turtles (Chelonia mydas) were examined for parasitic pathogens. Four species of cardiovascular flukes (Digenea: Spirorchiidae), Learedius learedi, Hapalotrema postorchis, Monticellius indicum and Amphiorchis solus were collected from 39 of 40 of the turtles, and Neospirorchis species were identified in seven of the 47 by histological examination. The pathological changes associated with the spirorchiids and their eggs included aneurysms, arteritis of great vessels with dark nodular thickenings, endocarditis, haemorrhagic lesions, thrombi, vasculitis, and granulomatous reactions in all the turtles. Ozobranchus branchiatus (Hirudinea: Ozobranchidae) leeches were found on the skin of 27 of the 47 turtles and were associated with traumatic purulent and ulcerative dermatitis. Oesophagitis associated with Rameshwarotrema uterocrescens (Digenea: Pronocephalidae) was recorded in 11 of 43 of the turtles. Petechial haemorrhages and unspecific crater-like ulcerated lesions on the gastric mucosa associated with Charaxicephaloides species and Charaxicephalus robustus (Digenea: Pronocephalidae) were observed in four of 40 of the turtles. Cholycystitis and ectasia of mucosal glands associated with Rhytidodoides similis (Digenea: Rhytidodidae) were observed in one of the 47 turtles. Fibropapillomas were observed on the skin of one turtle and fibromas on the skin of two of them.